2004
DOI: 10.1016/j.visres.2004.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Curvature population coding for complex shapes in human vision

Abstract: In the primate visual system relatively complex patterns such as curved shapes are first represented at intermediate levels of the ventral pathway. Furthermore, there is now evidence for the existence of curvature population coding in primate V4. We sought to determine whether similar encoding occurs in the human visual system by using a context-dependent lateral masking paradigm. In this paradigm a central closed contour comprising the test pattern is masked by surrounding larger or smaller patterns with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 34 publications
5
56
2
Order By: Relevance
“…Although our study did not test other stimuli related to local-global pattern processing, previous psychophysical studies have shown similar effects on localglobal pattern processing using different stimuli (e.g., radial frequency patterns; Habak, Wilkinson, Zakher, & Wilson, 2004;Wilkinson, Wilson, & Habak, 1998). Brain imaging studies on local-global tasks using other types of stimuli (Navon figures (Navon, 1977), parametrically degraded objects, etc.)…”
Section: Discussionmentioning
confidence: 83%
“…Although our study did not test other stimuli related to local-global pattern processing, previous psychophysical studies have shown similar effects on localglobal pattern processing using different stimuli (e.g., radial frequency patterns; Habak, Wilkinson, Zakher, & Wilson, 2004;Wilkinson, Wilson, & Habak, 1998). Brain imaging studies on local-global tasks using other types of stimuli (Navon figures (Navon, 1977), parametrically degraded objects, etc.)…”
Section: Discussionmentioning
confidence: 83%
“…Circles and RF patterns (Habak et al, 2004; Wilkinson et al, 1998) . Circles are the particular case of an RF pattern (see Figure 2) where the amplitude of modulation of the radius is zero.…”
Section: Methodsmentioning
confidence: 99%
“…The high sensitivity for discriminating amplitude modulations of radial frequency patterns provides strong evidence that shape perception is driven by a global mechanism that combines information across the circumference of the contour Habak, Wilkinson, & Wilson, 2006;Hess et al, 1999;Jeffrey, Wang, & Birch, 2002;Loffler et al, 2003;Schmidtmann et al, 2012;Wilkinson et al, 1998). This global pooling mechanism appears to be restricted to shapes with low radial frequency modulation (Schmidtmann et al, 2012;Wilkinson et al, 1998) and to be tuned to a specific type of shape and amplitude of radial modulations (Bell, Dickinson, & Badcock, 2008;Bell & Kingdom, 2009;Habak, Wilkinson, Zakher, & Wilson, 2004;Schmidtmann et al, 2012Schmidtmann et al, , 2013. Furthermore, several studies have shown that the inputs to the global pooling stage are themselves outputs of intermediate stage curvature detectors that integrate local orientation information to encode curvature and inflection points along the contour (Bell et al, , 2010(Bell et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%